О науке и цивилизации: воспоминания, мысли и размышления ученого / В. С. Емельянов - Емельянов Василий Семенович (Мысль, 1986)
Экземпляры: КХ (20170315) / Инвентарный номер: 879061 / Цена: 1.30 / Сис.шифр: 001 / Авт.знак: Е60 / ГРНТИ: 03 / ББК: 72